1985
DOI: 10.1002/ajmg.1320220114
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of chromosome 8p21.1→8pter: Case report and review of the literature

Abstract: The clinical manifestations and cytogenetic changes of a patient with 46,XY,del(8)(p21.1) are compared with those of nine other patients with a similar deficiency of chromosome 8. Patients with this chromosome anomaly have a syndrome of postnatal growth retardation, microcephaly, mental retardation, epicanthal folds, posteriorly angulated and malformed ears, short neck, relatively increased internipple distance, and congenital heart defect. A short and broad nose, a wide and flat nasal bridge, and a small jaw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
2

Year Published

1988
1988
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 18 publications
2
29
0
2
Order By: Relevance
“…It is suggested that pre-and postnatal growth retardation, microcephaly, mild facial anomalies, and moderate to severe mental retardation are consistent findings both in patients with del(8)(p21.1) [Digilio et al, 1998;Dobyns et al, 1985] and in patients with more terminal deletions in 8p23.1 [Hutchinson et al, 1992;Wu et al, 1996]. Adaptation difficulties at birth and feeding difficulties during the first months were frequent.…”
Section: Discussionmentioning
confidence: 92%
“…It is suggested that pre-and postnatal growth retardation, microcephaly, mild facial anomalies, and moderate to severe mental retardation are consistent findings both in patients with del(8)(p21.1) [Digilio et al, 1998;Dobyns et al, 1985] and in patients with more terminal deletions in 8p23.1 [Hutchinson et al, 1992;Wu et al, 1996]. Adaptation difficulties at birth and feeding difficulties during the first months were frequent.…”
Section: Discussionmentioning
confidence: 92%
“…Deletions that include band 8p23.1 are associated with congenital heart defects, microcephaly, growth retardation, intellectual disability, and a characteristic hyperactive, impulsive behavior [Dobyns et al, 1985;Claeys et al, 1997;Devriendt et al, 1999]. Haploinsufficiency for the GATA4 gene in 8p23.1 is thought to be responsible for congenital heart defects in patients with deletions of this region [Pehlivan et al, 1999].…”
Section: Discussionmentioning
confidence: 97%
“…In the liveborn. partial monosomies have been reported, such as deletion of the segment 8pter-»p21.1, most of which arose de novo (Dobyns et al, 1985). Breaks such as those observed in sperm chromosomes conceivably represent an example of this type of de novo abnor mality, since the acentric part of a broken chromosome would be lost at mitosis.…”
Section: Discussionmentioning
confidence: 99%